2016
DOI: 10.1136/jnnp-2015-312037
|View full text |Cite
|
Sign up to set email alerts
|

Safety and diagnostic value of brain biopsy in HIV patients: a case series and meta-analysis of 1209 patients

Abstract: Early brain biopsy may be indicated in HIV patients with focal brain lesion. This study aimed to evaluate and compare the safety and diagnostic value of brain biopsy in HIV patients in the pre-highly active antiretroviral therapy (HAART) versus post-HAART era via meta-analysis. Appropriate studies were identified per search criteria. The local database was retrospectively reviewed to select a similar patient cohort. Patient demographics, brain biopsy technique, histopathology and patient outcomes were extracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 55 publications
1
15
0
1
Order By: Relevance
“…[20,21] In our centre, the indication for early biopsy was, in 100% of cases, attributable to a low diagnostic presumption of CNS toxoplasmosis, which reflects the high negative predictive value of the combination of imaging studies and serology. [2,3,14,20] In agreement with previous studies on biopsies in HIVinfected patients, the morbidity and mortality of the procedure were low. In our study, the most frequent complication was infection of the surgical site, whereas in previous reports, bleeding was the most prevalent complication [2,7,10,14,17,21].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…[20,21] In our centre, the indication for early biopsy was, in 100% of cases, attributable to a low diagnostic presumption of CNS toxoplasmosis, which reflects the high negative predictive value of the combination of imaging studies and serology. [2,3,14,20] In agreement with previous studies on biopsies in HIVinfected patients, the morbidity and mortality of the procedure were low. In our study, the most frequent complication was infection of the surgical site, whereas in previous reports, bleeding was the most prevalent complication [2,7,10,14,17,21].…”
Section: Discussionsupporting
confidence: 89%
“…Gildenberg et al described the results of 250 biopsies between 1984 and 1998 with a diagnostic success rate of 94% [15]. In a recent meta-analysis that included 1209 patients from 26 studies, diagnostic success was reported as between 75 and 100%, with a change in therapeutic management based on biopsy results of 57.7% [3]. Although in our centre the percentage of diagnostic success for histology was lower, the procedure allowed us to obtain material in order to perform other complementary diagnostic methods in addition to histology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[41] Unfortunately, brain biopsy is invasive while conventional imaging modalities have limited diagnostic accuracy. [6,12] Functional nuclear imaging modalities such as SPECT and PET have become increasingly popular diagnostic tools, as they provide images with high spatiotemporal resolution to evaluate perfusion or metabolism. SPECT relies on gamma ray emission from uptake of radiotracers such as Tc-99m, while PET utilizes positron-emitting radiotracers such as 18 F-fluorodeoxyglucose.…”
Section: Discussionmentioning
confidence: 99%
“…Brain biopsy, despite being the current diagnostic gold standard, is invasive and has high morbidity. [12] Over the past few decades, noninvasive functional nuclear imaging modalities such as single-photon emission computed tomography (SPECT) and positron emission tomography (PET) have been used to detect PCNSL based on physiologic differences between lymphoma and infectious lesions. Several studies have shown high diagnostic accuracy of both SPECT [10,13–17] and PET, [1823] but a few other studies have cast doubt on the utility of SPECT.…”
Section: Introductionmentioning
confidence: 99%